Pengaruh Perkembangan Filsafat Ilmu terhadap Ilmu Pengetahuan Kontemporer - Intan Dwi Rahayu; Jannatun Naim (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2023)
The development of the philosophy of science plays a crucial role in shaping the direction and character of contemporary science. Philosophy of science not only examines the ontological, epistemological, and axiological foundations of scientific knowledge, but also functions as a reflective framework for understanding paradigm shifts, research methodologies, and ethical dimensions in scientific practice. This article aims to analyze the influence of the development of philosophy of science on contemporary science, particularly in relation to changes in scientific paradigms, the strengthening of methodological pluralism, and the growing awareness of ethical responsibility. This study employs a qualitative approach using a library research method through the analysis of relevant philosophical and contemporary scientific literature. The findings indicate that developments in the philosophy of science have encouraged a shift from positivistic perspectives toward more critical, reflective, and contextual approaches. Furthermore, philosophy of science contributes to the recognition of science as a value-laden social practice rather than a value-free activity. Ethical awareness and social responsibility are therefore essential elements of contemporary scientific practice. In conclusion, philosophy of science serves as a conceptual foundation that ensures scientific development is oriented not only toward empirical truth, but also toward values, meaning, and benefits for human life.